Sequential explanatory analysis of environmental awareness towards responsible environmental behavior (REB) of high school students in Depok City, West Java, Indonesia - Novia El Savada; Eka Suhardi; Rita Istiana (Indonesian Journal of Applied Environmental Studies, 2021)
Objective of this study is to obtain information about the interrelationship between environmental awareness and the responsible environmental behavior of high school students. Research conducted toward students of the Masjid Terminal  High School (SMA) at Depok City in December 2019 to July 2020 with samples of 111 respondents by proportional random sampling technique. A mix-method was employed in this study, which is a combination of quantitative and qualitative methods as sequential explanatory. Collection of quantitative data was conducted using a questionnaire with rating scale for X and Y variables. The validity test used Pearson's product moment and the reliability test used alpha Cronbach. The analysis of quantitative data with a prerequisite test in the form of a normality test employed the Kolmogorov-Smirnov test and a homogeneity test using a Levine statistic. Testing the data hypothesis was using the correlation test with Pearson product moment using SPSS 26. Qualitative research data was obtained from the interviews, and the data was analyzed by reducing data, presenting data and drawing conclusions. The results showed that there was a positive correlation between environmental awareness and responsible environmental behavior with the regression equation Å¶ = 99.939 + 0.161x with a correlation coefficient of r = 0.195 and r2 of 3.80%. The contribution of r2 means that 3.80% of responsible environmental behavior is influenced by environmental awareness, while 96.20% is influenced by other factors. Based on above results, can be conclude that there are positive correlation between environmental awareness and responsible environmental behavior which influenced by the factors of family background, habits, information, as well as social environment.Tujuan penelitian ini adalah untuk memperoleh informasi tentang hubungan antara kesadaran lingkungan dengan perilaku tanggung jawab lingkungan pada siswa SMA. Penelitian dilakukan terhadap siswa sekolah (SMA/High School) Masjid Terminal, Kota Depok, Jawa Barat, pada bulan Desember 2019 hingga Juli 2020 dengan jumlah sampel 111 responden dengan teknik proporsional random sampling. Mix-method digunakan dalam penelitian ini, yang merupakan kombinasi antara metode kuantitatif dan kualitatif sebagai sequential explanatory. Pengumpulan data kuantitatif dilakukan dengan menggunakan kuesioner dengan skala sikap (rating scale) untuk variabel X dan Y. Uji validitas menggunakan Pearsons product moment dan uji reliabilitas menggunakan alpha Cronbach. Analisis data kuantitatif dengan uji prasyarat berupa uji normalitas menggunakan uji Kolmogorov-Smirnov dan uji homogenitas menggunakan statistik Levine. Pengujian hipotesis data menggunakan uji korelasi dengan Pearsons product moment menggunakan SPSS 26. Data penelitian kualitatif diperoleh dari wawancara, dan data dianalisis dengan mereduksi data, menyajikan data dan menarik kesimpulan. Hasil penelitian menunjukkan bahwa terdapat hubungan positif antara kesadaran lingkungan dengan perilaku tanggung jawab lingkungan dengan persamaan regresi Å¶ = 99,939 + 0,161x dengan koefisien korelasi r = 0,195 dan r2 sebesar 3,80%. Kontribusi r2 berarti 3,80% perilaku tanggung jawab lingkungan dipengaruhi oleh kesadaran lingkungan, sedangkan 96,20% dipengaruhi oleh faktor-faktor lain. Berdasarkan hasil di atas, dapat disimpulkan bahwa terdapat hubungan positif antara kesadaran lingkungan dengan perilaku tanggung jawab lingkungan yang dipengaruhi oleh faktor latar belakang keluarga, kebiasaan, informasi, serta lingkungan sosial.